Bahasa Inggris - Zico Junius Fernando; Yagie Sagita Putra; Ria Anggraeni Utami (UNUSA Press, 2022)
The spread of drugs is almost unavoidable. Given that almost the entire world's population can easily get drugs from irresponsible people. Today, drug abuse has reached an alarming situation that has become a state problem. This is very concerning because victims of narcotics abuse in Indonesia have recently tended to increase and include limited groups of people who can afford it and penetrated the underprivileged community and involve children or young teenagers, something that is somewhat difficult. It's worrying considering that they are the generation that hopes to continue the nation's survival in honor. As one of the efforts to prevent drug abuse among the younger generation at Al-Ma'un Shelter Bengkulu, the PPM team intends to educate and increase understanding of the children of the Al-Ma'un Shelter also children's parents. Regarding drug abuse among young people. With the proposed community service, it is hoped to increase education and understanding and legal awareness of the children of the Al-Ma'un Shelter in Bengkulu City as a form of child protection.